Using Gravity Anomaly for Subsurface Modeling and Earthquake Hypocenter for Active Fault Characterization in West Sulawesi - Siti Purnawasih; Muhardi Muhardi; Radhitya Perdhana (BULETIN FISIKA, 2026)
An active fault triggered the earthquake in West Sulawesi on 15 January 2021, because this region has high tectonic activity. This study aims to model the subsurface and characterize active faults using gravity anomaly and earthquake hypocenter data, respectively. Gravity anomaly data at 2,640 measurement points were obtained from the TOPEX satellite, while earthquake hypocenter data for the 2011-2021 period were obtained from the USGS, IRIS, and Geofone websites. A complete Bouguer anomaly (CBA) distribution was obtained from free air anomaly (FAA) and topographic data using terrain and Bouguer corrections. The 2D modeling of subsurface geological structures was performed based on the regional anomaly distribution obtained by subtracting the complete Bouguer anomaly from the residual anomaly. Determining the earthquake focal mechanism uses the tensor moment method, which is represented visually as a beachball. The results show a regional anomaly distribution of 30-86 mGal. The 2D modeling shows that the subsurface consists of nine rock formations: Mandar Formation, Mapi Formation, Intrusive Rocks, Talaya Volcanic Rocks, Latimojong Formation, Intermontane Deposits, Mamuju Formation, Tapalang Member, and Adang Volcanic Rocks. Based on the earthquake focus mechanism, represented visually as a beach ball, six active faults were identified: two thrust faults, three strike-slip faults, and a normal fault.